Assessment of Malaysian brown seaweed Padina gymnospora antioxidant properties and antimicrobial activity in different solvent extractions - Nazarudin, Muhammad Farhan; Shahidan, Muhammad Syazwan; Noor Mazli, Nur Amirah Izyan; Tan, Hui Teng; Yam, Sim Khaw; Md Yasin, Ina Salwany; Isha, Azizul; Paiko, Mohammed Aliyu (Springer Japan, 2022)
The combination of a proton nuclear magnetic resonance (1H-NMR)-based metabolomics approach and principal component analysis (PCA) was used to differentiate variations of active metabolites in Padina gymnospora subjected to different extraction solvents. Their proximate composition and phytochemical, antioxidant, and antimicrobial activity were also evaluated. A total of 13 metabolites were identified in the different solvents (polar, semipolar, and nonpolar) via 1H-NMR analysis. The present study demonstrated that P. gymnospora brown seaweed was rich in protein, lipid, and carbohydrates. Phytochemical investigation of the different P. gymnospora extracts revealed various secondary metabolites. The most abundant essential amino acid was leucine [5.79 ± 0.06 mg g−1 dry weight (DW)], and the most abundant nonessential amino acid was glutamic acid (8.62 ± 0.04 mg g−1 DW). The presence of metabolites such as alanine, N-phenylacetylphenylalanine, glutamic acid, 2-hydroxyisobutyric acid, sarcosine, and π-methylhistidine in the seaweed extracts was strongly correlated with their level of 2,2-diphenyl-1-picrylhydrazyl (DPPH) free-radical scavenging activity. P. gymnospora appeared to have antibacterial activity against Staphylococcus aureus (ATCC 43,300). The study also revealed P. gymnospora’s potential for use as a rich source of antioxidant agents, implying that commercial cultivation of this seaweed may be incentivized.